2016
DOI: 10.1002/jbio.201500252
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer diagnosis by optical coherence tomography: First results from a needle based optical platform for tissue sampling

Abstract: The diagnostic accuracy of Optical Coherence Tomography (OCT) based optical attenuation coefficient analysis is assessed for the detection of prostate cancer. Needle-based OCT-measurements were performed on the prostate specimens. Attenuation coefficients were determined by an earlier described in-house developed software package. The mean attenuation coefficients (benign OCT data; malignant OCT data; p-value Mann-Whitney U test) were: (3.56 mm(-1) ; 3.85 mm(-1) ; p < 0.0001) for all patients combined. The are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…91 Furthermore, several authors confirmed the feasibility of needle-based OCT for differentiation between benign and malignant prostatic tissues. [93][94][95][96]…”
Section: Octmentioning
confidence: 99%
“…91 Furthermore, several authors confirmed the feasibility of needle-based OCT for differentiation between benign and malignant prostatic tissues. [93][94][95][96]…”
Section: Octmentioning
confidence: 99%
“…In our measurements data will be obtained from invivo tissue, in which red blood cells will absorb and scatter light different from regular cells. Due to the perfusion of prostate tissue, the acquired data will most probably differ from the ex-vivo measurements [29,41]. Nonetheless, this study will enable us to understand the in-vivo OCT and CLE images and challenges in co-localization of acquired in-vivo data with ex-vivo histology; shrinkage of the prostate tissue (44,45), histology comparison with forward-looking CLE data or OCT data and exact location determination.…”
Section: Benefits and Risksmentioning
confidence: 99%
“…A limited number of studies has looked at OCT's diagnostic role in differentiating benign and malignant microscopic tissue of the prostate gland. Muller et al demonstrated with the use of a histopathological validation tool that ex-vivo needle-based OCT measurements of radical prostatectomy specimens can differentiate between cancer and healthy prostate tissue [27][28][29]. The quantitative analysis of OCT signal by means of the attenuation coefficient was significantly higher in malignant compared to benign tissue with an area under the curve ranging from 0.64 -0.89 depending on the histopathological analysis used [29].…”
mentioning
confidence: 99%
“…In organs with high tissue heterogeneity, such as the prostate, one‐to‐one registration with the histological specimen is required. Previous work has shown the possibility to acquire needle‐based OCT data in human prostate and relate this to benign or malignant tissue, qualitatively and quantitatively . Prostate tissue, however, cannot only be categorized as benign or malignant but contains many different tissue types, and therefore analysis of whole‐mount data is required.…”
Section: Introductionmentioning
confidence: 99%